Alkaloid Composition and Antiarrhythmic Activity of the Extracts from Rauvolfia serpentina Tissue Culture - Khromov, Aleksandr; Dobrelia, Natalia; Konvalyuk, Iryna; Bieda, Oleksandr; Andreev, Igor; Mozhylevska, Ludmyla; Yarmoluk, Sergiy; Soloviev, Anatoliy; Kunakh, Viktor (Planta Medica, 2025)
Rauvolfia serpentina produces a number of indole alkaloids and has long been used in the traditional treatment of arrhythmia. Given the shortage of natural resources, the K-27M strain of R. serpentina tissue culture was established. The aim was to evaluate the antiarrhythmic activity of extracts with different compositions and ratios of indole alkaloids derived from the cell biomass of the K-27M strain. Chemical analysis was conducted using HPLC-MS. Adrenaline-induced (rats) and ischemia-reperfusion arrhythmia (isolated guinea pig hearts) models were used to study the antiarrhythmic activity of the extracts. Extracts were obtained from dry (extracts 1, 2, and 3) and fresh biomass (fractions 1 and 2 of extract 4). Extract 1 contained ajmaline and acetylajmaline (the total indole alkaloid content (TIAC) was 2.2% of the dry biomass); extract 2–ajmaline, acetylajmaline, and raucaffricine (TIAC 6.4%); extract 3–ajmaline and raucaffricine (TIAC 29.0%). Fraction 1 of extract 4 was dominated by vomilenine, methylajmalicine, ajmalicine, and raufloridine (TIAC 65.0%), and fraction 2 of extract 4 contained acetylajmaline (TIAC 47.4%). Extracts 1 and 2 containing negligible amounts of indole alkaloids showed a weak proarrhythmic effect. Fractions 1 and 2 of extract 4 had a pronounced antiarrhythmic effect in the adrenaline-induced arrhythmia model. In addition, fraction 2 of extract 4 had an antiarrhythmic effect in the ischemia-reperfusion arrhythmia model. The level of this activity depended on the composition and ratio of alkaloids in the extract. Thus, the K-27M strain of R. serpentina tissue culture is a promising source of indole alkaloids with antiarrhythmic activity.
Keywords: Rauvolfia serpentina; Apocynaceae; tissue culture; indole alkaloids; antiarrhythmic effect; adrenaline-induced arrhythmia model; ischemia-reperfusion arrhythmia model